Effects of Improving Recyclable Plastic Bottles as Classroom Decoration on Grade 12 Accountancy, Business, and Management Strand Students at Bestlink College of the Philippines, S.Y. 2019–2020 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The researcher focused on the effects of improving recyclable plastic bottles as a classroom decoration, which may enhance their multiple skills. “Recycling today for a better tomorrow.” Recycling is the process of enhancing an existing product that may bring some effects on people in the future. The quotation above indicated that recycling can be beneficial to anyone. Plastic recycling refers to the process of recovering waste or scrap plastic and reprocessing the materials into functional and useful products. Thus, the researchers decided to improve recyclable plastic bottles and determine their effects. The school is experiencing an environmental problem, that is, plastic waste pollution. The purpose of this study was to improve the students’ skills. The importance of this study was to determine the positive and negative effects of plastic recycling. The study used descriptive design and qualitative research. This study included 50 selected grade 12 Accountancy, Business, and Management (ABM) Strand students. Nine variables were considered to determine the effects of improving recyclable plastic bottles as classroom decorations. The method used was a survey. The researchers used convenience sampling because it is easy to use, along with its other research advantages. In pilot studies, a convenience sample was used because it allowed the researcher to obtain basic data and trends regarding his study without the complications of using a randomized sample. The result of this study improved the skills of Grade 12 ABM Strand students in recycling plastic bottles in terms of environmental cleanliness, saving money, creating trash, and the time needed. The study revealed that improving recyclable plastic bottles as classroom decorations has a remarkable impact on students’ learning because it can boost them to think actively and show their skills. The researchers provided the following recommendations. The students should improve their skills, and parents should guide their children in their learning. Teachers should also help their students to become responsible. The school administration also needs to implement an “eco-friendly school zone.” Lastly, future researchers can use this study as their reference.
Keywords: recycling, scrap, plastic bottles